Mediator Syukur dan Sabar pada Dukungan Sosial dan Stres Tenaga Kesehatan selama Pandemi COVID-19 - Farra Anisa Rahmania; Fuad Nashori (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
This study aims to analyze the correlation between social support and stress towards the health workers during COVID-19 pandemic mediated by gratitude and patience. This study used quantitative correlational approach on 245 health workers. This study used four scales, Perceived Stress Scale, Multidimensional Scale Perceived Social Support, Gratitude Scale, and Patience Scale. The data analysis used the mediation analysis by JASP 14.1. The results showed that the model of social support and stress among the health workers with the mediation of gratitude and patience was not supported by data. After further analysis, it shows that gratitude had a role as a partial mediator between social support and stress among the health workers during COVID-19 pandemic.